KNOWLEDGE AND AWARENESS OF THE POCSO ACT 2012 AMONG ADOLESCENTS IN ANANTHAPURAMU DISTRICT-A CROSS SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Child sexual abuse is a major public health concern with serious lifelong consequences. The Protection of Children from Sexual Offences (POCSO) Act, 2012 provides a comprehensive legal framework for protecting children in India. However, adolescents' awareness of the Act remains inadequate, limiting timely reporting and access to legal protection. This study assessed adolescents' knowledge of the POCSO Act and examined socio-demographic factors associated with knowledge levels. Methods: A school-based cross-sectional descriptive study was conducted among 200 adolescents aged 15–19 years studying in two government and two private colleges in urban Ananthapuramu district, Andhra Pradesh, India, from January to June 2026. Participants were selected using simple random sampling. Data were collected using a pretested, self-structured questionnaire comprising 20 multiple-choice questions on the POCSO Act. Knowledge scores ranged from 0–20 and were categorized as good (14–20) or poor (0–13). Results: Among the 200 participants, 120 (60.0%) were females and 104 (52.0%) attended government schools. Overall, 124 (62.0%) adolescents demonstrated good knowledge of the POCSO Act. Good knowledge was more common among females than males (66.7% vs. 55.0%; p=0.096) and among private school students than government school students (68.8% vs. 55.8%; p=0.058), although these differences were not statistically significant. Adolescents with literate parents had significantly higher knowledge than those with illiterate parents (68.4% vs. 41.7%; p